2016
DOI: 10.1111/jam.13283
|View full text |Cite
|
Sign up to set email alerts
|

Assessing an imidazolium salt's performance as antifungal agent on a mouthwash formulation

Abstract: This study demonstrates a new and effective antibiofilm formulation containing the IMS C MImCl. These findings suggest the IMS' use as mouthwash formulations active ingredient against Candida biofilms on oral surfaces, as it outperforms the often used cetylpyridinium chloride at a 10 times lower concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
11
0
2
Order By: Relevance
“…(Schrekker et al, 2016). Using contaminated acrylic resin strip specimens, 1-n-hexadecyl-3-methylimidazolium chloride was demonstrated as a strong antifungal for mouthwash formulation (Bergamo et al, 2016). Although several studies have reported antifungal activity, effect of imidazolium ionic liquids on preformed fungal biofilms (biofilm eradication potential) is largely unknown ( Table 1).…”
mentioning
confidence: 99%
“…(Schrekker et al, 2016). Using contaminated acrylic resin strip specimens, 1-n-hexadecyl-3-methylimidazolium chloride was demonstrated as a strong antifungal for mouthwash formulation (Bergamo et al, 2016). Although several studies have reported antifungal activity, effect of imidazolium ionic liquids on preformed fungal biofilms (biofilm eradication potential) is largely unknown ( Table 1).…”
mentioning
confidence: 99%
“…The MIC range for dermatophytes was 0.39‐3.12 µg/mL and for yeast was 0.78‐1.56 µg/mL, reinforcing the data from the screening that this compound is actually active at very low concentrations. In other studies, the presence of chlorine in chemical structures investigated as to the antifungal application has already been verified as determinant for effective activity . Structurally, the position of the chlorine is important for improving the antifungal action, since the substitution at positions meta and para of the disubstituted molecule 2j was more advantageous (lower MICs) than the substitution at ortho and para positions as for 2i (Figure ).…”
Section: Resultsmentioning
confidence: 85%
“…In other studies, the presence of chlorine in chemical structures investigated as to the antifungal application has already been verified as determinant for effective activity. 37,[45][46][47] Structurally, the position of the chlorine is important for improving the antifungal action, since the substitution at positions meta and para of the disubstituted molecule 2j was more advantageous (lower MICs) than the substitution at ortho and para positions as for 2i (Figure 1). These with some compounds of the same class investigated in this study:…”
Section: In Vitro Susceptibility and Structure-activity Relationshipmentioning
confidence: 99%
“…As adesinas são enzimas encontradas nos microrganismos que apresentam receptores específicos na película adquirida ou nas células epiteliais da boca 38,39 . Diversos são os sintomas clínicos relatados pelos pacientes: dor, halitose, prurido e percepção de queimação podem acontecer pelo fato de a C. albicans produzir exoenzimas, constituídas principalmente por proteinases que facilitam a adesão do biofilme, e também devido a fatores do hospedeiro, tais como redução do pH, do fluxo salivar e da microbiota oral 40 41,42 . Para as cepas de C. tropicalis e C. parapsilosis, é notória a presença de blastoconídios e pseudo-hifas.…”
Section: Espécies De Candida Formadoras De Biofilme Em Resinas Acrílicasunclassified
“…Bergamo et al 40 Avaliação da atividade do miconazol em biofilmes maduros de Candida (C. albicans, C. glabrata, C. tropicalis e C. parapsilosis) in vitro formados em discos de PMMA.…”
unclassified